Evaluation of the surface water quality of Al-Sin Spring and 16th of Tishreen Dam Lake using some quality indicators and comparison between them for drinking purposes - خلوف نسرين (Latakia University Journal -Engineering Sciences Series, 2023)
An assessment of the water quality was conducted in the two lakes of the 16th of Tishreen Dam and Lake Al-Sin during the year 2021-2022 by measuring a number of important physical and chemical criteria in determining water quality, which included temperature, pH, electrical conductivity, turbidity, nitrates, nitrites and phosphates. ...etc. The measurement results were represented graphically and the results were compared with the Syrian standard specification for drinking purposes, and we evaluated the water quality of the 16th of Tishreen Dam lakes and Al-Sin Lake by calculating the following quality indicators: the NSF WQI index, the weighted arithmetic index, and the Canadian index, and the results showed that there are some of the measured values It is not in accordance with the standard, especially in the point of the 16th of Tishreen Dam lake, due to the waste water being thrown into the lake, and because it is stagnant water exposed to the growth of algae, so the water must be subjected to good treatment before use. And the presence of low concentrations of nitrates in the point of the spring of Al-Sun compared to the point of Lake of the 16th of Tishreen Dam as a result of its transformation into nitrite in the lake. The results of the NSF QWI index method were incorrect, due to a lack of the number of parameters involved in the calculation. It was concluded that all methods of quality evidence gave preference to the water of the first point in the spring of Al-Sin.